SATELLITE AERONAVIGATION CENTER OF NATIONAL AVIATION UNIVERSITY - Kharchenko, V.P.; Konin, V.V. (Proceedings of National Aviation University (archive), 2005)
Satellite Aeronavigation Center of National Aviation University is presented: research directions, laboratory practicum, research equipment, developed problems.